FoCUS cardiac ultrasound training for undergraduates based on current national guidelines: a prospective, controlled, single-center study on transferability - Weimer, Johannes Matthias; Rolef, Peter; Müller, Lukas; Bellhäuser, Henrik; Göbel, Sebastian; Buggenhagen, Holger; Weimer, Andreas; Waezsada, Elias; Kirchhoff, Friederike; Weinmann-Menke, Julia (BMC medical education, 2023)
In emergency and critical-care medicine, focused cardiac ultrasound (FoCUS) is indispensable for assessing a patient’s cardiac status. The aim of this study was to establish and validate a peer-to-peer-supported ultrasound course for learning FoCUS-specific skills during undergraduate studies at a German university.